Estruturas gravadas em cristal de niobato de lítio por exposição a pulsos laser de femtossegundos: produção e caracterização - Oliveira, Fernanda Mantuan Dala Rosa de (2018)
The present work shows the method used to write structures in lithium niobate crystals doped with erbium and magnesium as well as the characterization of such structures. Structures were produced in a x-cut sample by the direct inscription with femtosecond laser pulses. The produced structures showed stability over time and optical guiding ability. The recording parameters produced waveguides of Type II, whose main characteristic is the decrease of the ordinary and extraordinary refractive indices at the focal point of the recording laser, with increase of the extraordinary refractive index in the region of stress around the focus. The structures are anisotropic with regions that guide light with different states of polarization. Consequently, for a specific application, the operation region can be chosen according to the polarization state of the coupled light.